Identification of Cell-Surface Proteins Endocytosed by Human Brain Microvascular Endothelial Cells In Vitro - Shingo Ito; Mariko Oishi; Seiryo Ogata; Tatsuki Uemura; Pierre-Olivier Couraud; Takeshi Masuda; Sumio Ohtsuki (MDPI AG, 2020)
Cell-surface proteins that can endocytose into brain microvascular endothelial cells serve as promising candidates for receptor-mediated transcytosis across the blood-brain barrier (BBB). Here, we comprehensively screened endocytic cell-surface proteins in hCMEC/D3 cells, a model of human brain microvascular endothelial cells, using surface biotinylation methodology and sequential window acquisition of all theoretical fragment-ion spectra-mass spectrometry (SWATH-MS)-based quantitative proteomics. Using this method, we identified 125 endocytic cell-surface proteins from hCMEC/D3 cells. Of these, 34 cell-surface proteins were selectively internalized into human brain microvascular endothelial cells, but not into human umbilical vein endothelial cells (HUVECs), a model of human peripheral microvascular endothelial cells. Two cell-surface proteins, intercellular adhesion molecule-1 (ICAM1) and podocalyxin (PODXL), were identified as BBB-localized endocytic cell-surface proteins in humans, using open mRNA and protein databases. Immunohistochemical evaluation confirmed PODXL expression in the plasma membrane of hCMEC/D3 cells and revealed that anti-PODXL antibody-labeled cell-surface PODXL internalized into hCMEC/D3 cells. Immunohistochemistry further revealed that PODXL is localized at the luminal side of human brain microvessels, supporting its potential suitability for translational applications. In conclusion, our findings highlight novel endocytic cell-surface proteins capable of internalizing into human brain microvascular endothelial cells. ICAM1 or PODXL targeted antibody or ligand-labeled biopharmaceuticals and nanocarriers may provide effective targeted delivery to the brain across the BBB for the treatment of central nervous system (CNS) diseases.